Salinity threshold for phosphorus limitation in an estuary-coast continuum - Cai, Shujie; Liu, Weiran; Tong, Zhuyin; Lin, Lizhen; Ou, Linjian; Xiao, Wupeng; Huang, Bangqin (Frontiers in Marine Science, 2024)
River-derived nutrient imbalances can induce phosphorus (P) limitation in coastal plankton, but the salinity thresholds that govern this phenomenon have received little attention. Here, we provide a first insight into threshold responses in P-limitation along the salinity gradient in coastal ecosystems. Our seasonal sampling in the northern South China Sea showed a clear nonlinear decrease in alkaline phosphatase activity (APA) with increasing salinity. A pivotal finding was the identification of a salinity threshold at 32.83, presenting an early-warning indicator for P-limitation detection. Using a mixed-effects model, we further revealed that the robust positive correlation between phytoplankton biomass and APA gradually weakened as salinity increased toward this threshold. This implies a shift in phytoplankton’s P-limitation at this salinity threshold and the contribution of heterotrophic bacteria in APA within high-salinity seawater. These insights highlight the importance of refining monitoring strategies with salinity and APA dynamics as early-warning indicators for nutrient limitation in coastal ecosystems.